Pengembangan Permainan Congklak Integritas sebagai Sarana Pendidikan Anti Korupsi Siswa - Guntoro, Muhammad Yogi; Pratomo, Sigit Adhi; Ferdiana, Septin Gis (Journal of Moral and Civic Education, 2024)
Corruption is a major impediment to the nation's social, economic, and political development, making early anti-corruption education crucial. This article discusses the role of the traditional game congklak as a learning medium for instilling anti-corruption values in Indonesia's younger generation. This study employs the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) to develop a congklak game that teaches values such as honesty, integrity, responsibility, and sportsmanship. The findings indicate that using congklak significantly enhances students' understanding of anti-corruption values. The game provides an interactive experience that helps students internalize essential values and comprehend their relevance to daily life. Despite its effectiveness, challenges remain, such as younger students' difficulty in grasping modified rules and longer-than-expected game duration. However, with appropriate adjustments, congklak can be integrated into character education curricula, preserving local culture while supporting the vision of Indonesia Emas 2045 as a nation of high integrity. This study presents an innovative approach to anti-corruption education through culturally relevant, local traditions.